2015
DOI: 10.1158/2159-8290.cd-15-0246
|View full text |Cite
|
Sign up to set email alerts
|

Paralog-Specific Kinase Inhibition of FGFR4: Adding to the Arsenal of Anti-FGFR Agents

Abstract: Summary:In this issue of Cancer Discovery , Hagel and colleagues report the design and the in vitro and in vivo activity of a novel, irreversible, paralog-specifi c kinase inhibitor of FGFR4, BLU9931. This compound binds covalently to a cysteine residue in the hinge region of FGFR4 but not in FGFR1-3. BLU9931 induces tumor shrinkage in hepatocellular carcinoma models that express a functioning ligand/receptor complex consisting of FGF19/ FGFR4/KLB and adds to a growing list of anti-FGFR4 agents. Cancer Discov;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…In this study, we have shown that inhibiting FGFR4 using a selective small molecule may provide therapeutic benefit to a subset of HCC patients with FGF19 overexpression. Although pan-FGFR inhibitors are undergoing clinical evaluation for a variety of indications, they are likely unsuitable for FGF19-driven HCC due to their low potency against FGFR4 (11). We exploited the unique hinge cysteine in the FGFR4 kinase domain to design a covalent inhibitor, H3B-6527, that specifically inhibits FGFR4 and largely spares other FGFRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we have shown that inhibiting FGFR4 using a selective small molecule may provide therapeutic benefit to a subset of HCC patients with FGF19 overexpression. Although pan-FGFR inhibitors are undergoing clinical evaluation for a variety of indications, they are likely unsuitable for FGF19-driven HCC due to their low potency against FGFR4 (11). We exploited the unique hinge cysteine in the FGFR4 kinase domain to design a covalent inhibitor, H3B-6527, that specifically inhibits FGFR4 and largely spares other FGFRs.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest targeting FGFR4 would have therapeutic benefit in HCC with altered FGF19 signaling. While a number of pan-FGFR inhibitors are being clinically evaluated in a variety of indications, they display poor potency against FGFR4 potentially limiting their application to FGF19-driven HCC (11). Furthermore, pan-FGFR inhibitors with FGFR4 potency would likely be limited by their on-target FGFR1-3-mediated dose-limiting toxicities (hyperphosphatemia and soft-tissue mineralization), suggesting a need to improve FGFR4 selectivity (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in affinity of FGFR inhibitors for FGFR family members has been explored by structural and biophysical comparison and the crystal structure of the FGFR4 kinase domain has recently been revealed [34]. The first selective small molecule inhibitors aimed at FGFR4 have just been developed [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been widely postulated that the ability to selectivity inhibit a single isoform of FGFR may result in compounds with improved therapeutic margins. In particular, there is evidence that inhibition of FGFR1 is associated with mineralization in preclinical models and may cause doselimiting effects in the clinic [44].…”
Section: Isoform-selective Fgfr Inhibitorsmentioning
confidence: 99%